Donor-derived cytomegalovirus-cytotoxic T lymphocytes and leflunomide successfully control refractory cytomegalovirus infections and disease of multiple sites after allogeneic-hematopoietic stem cell transplantation: A case report - Su, Nan; Liu, Zhenghua; Sun, Peng; Gu, Feng; Yan, Xiaojing; Cai, Dali (Frontiers in Medicine, 2022)
Drug-resistant CMV infection post HSCT often leads to morbidity and mortality. Several studies have shown that CMV-CTLs can overcome resistant CMV infection, but still many questions remain unanswered. Here we present a case of refractory CMV infection post allogeneic HSCT. Donor derived CMV-CTLs failed to eliminate the virus in unique peripheral blood on the first application, when 70mg methylprednisolone was taken per day. After a second attempt with a combination of 8mg methylprednisolone with leflunomide, a complete and persisting clearance of all involved sites, including peripheral blood, urinary system, leptomeninges and retina was achieved . To summarize, intravenous infusion of CTLs can eliminate CMV in oculi and central nervous system and a low dosage of 8mg methylprednisolone has no interaction with CMV-CTLs.